Development of a Learning Experience Model, the PEDRA Model, On the Topic of "The Essence of Colors," To Enhance Hand-Eye Coordination for Young Children Aged 3-5 Years - Thipkrathok, Ladda (Research Community and Social Development Journal, 2025)
Background: The conceptual basis and necessity of organizing experiences that connect interests, practice, and develop skills of early childhood learners. The objectives are to study basic information, create and evaluate the effectiveness of the experience format, and assess its impact on promoting hand-eye coordination in young children aged 3-5 years. Methods: Research and development, including early childhood parents, teachers, personnel, experts, and young children, and senior experts. The target group of 75 was selected using purposive sampling. The study used an opinion assessment form, a literature review, an effectiveness assessment form, and a one-group pre-post quasi-experimental design. The tools, which include content validation, data collection through field surveys, focus groups, and interviews, organizing activities, experiments, and evaluations, have been tested. Data through field surveys, focus groups, interviews, activities, experiments, and estimates. The data were analyzed using mean and standard deviation, the 80/80 calculation, paired t-test, and content analysis. Results: Young children aged 3-5 years receive moderate learning experiences. Developed the PEDRA model for preparation, examples, hands-on practice, reflection, and application of knowledge. And the experience plan, according to the format, is most appropriate. The process and outcome efficiency met the 80/80 criteria, and the post-learning achievement was higher than before learning. Lastly, after the experience, coordination of hand and eye muscles was higher than before, resulting in the most satisfying and effective. Conclusions: The development of the PEDRA model on the essence of color is appropriate and highly effective for young children aged 3-5 years. Key findings from the implementation include: Young children who received learning experiences showed increased achievement. Improvements were in hand-eye coordination skills. Participants were the learning experience. The model’s success is appropriate for this age group and the effective delivery of the topic.